Perception and differences of manual and chemical weed control methods on yield and mangement cost of paddy in Ledang, Johor / Muhammad Shawal Akmar Mohd Idris - Mohd Idris, Muhammad Shawal Akmar (Faculty of Plantation and Agrotechnology, 2016)
The survey intended to obtained the perception and differences of manual and chemical weed control methods on yield and management cost of paddy. This survey was implemented using questionnaires by collecting samples population about 140 paddy farmers either using manual and chemical control method in Ledang, Johor. This survey aim to study the perception of weed control methods on yield of paddy, determine the differences of yield between these methods and determine which type that can give an advantage in term of costing operation. Data collected had been analyzed using Pearson's correlation, regression and T-test by using SPSS software. From this study, both correlation for manual and chemical control method, yield have significant relationship with production and labor. It means that the rate of deterioration and consistency will effect yield, skill and experience also closely related on the yield of paddy. It differ with cost that had no significant relationship with yield. Material did not had any impact toward yield if it's application was fully utilized. Regression analysis of manual method stated that labor factor is a dominant factor that contribute to the yield of paddy. Meanwhile, regression analysis for chemical method, production factor is dominant factor contribute to yield of paddy. In addition, r2 indicates for both methods that this model questionnaires are all that good to fits the data. Based on the T-test that had been obtained, comparison of the yield and costing operation between manual and chemical control method have significance difference which are the mean yield for chemical control higher than the manual control method in (ton / l acre). Also, the mean for the costing of manual and chemical control method respectively, indicate that chemical control have higher costing operation than manual control method. It can be concluded that yield of paddy and costing operation for chemical control method is much more higher than manual control method.